Accelerated Testing of Chromium Poisoning of Sr-Containing Mixed Conducting Solid Oxide Cell Air Electrodes - Beez, Alexander; Schiemann, Kevin; Menzler, Norbert H.; Bram, Martin (Frontiers in Energy Research, 2018)
A straightforward method for accelerated testing of Cr poisoning phenomena on mixed ionic and electronic conducting Solid Oxide Cell (SOC) air electrode materials was developed. Cr2O3-powder is mixed with an organic matrix and screen printed onto anode-supported button cells with (La,Sr)(Co,Fe)O3-δ (LSCF) cathode. Then, a thermal treatment was conducted to achieve the formation of a well-defined amount of SrCrO4 on the cathode surface within only a few hours. For the proof of concept, single cell measurements were done to investigate the influence of this new kind of Cr deposition. As reference, a cell poisoned via gas phase diffusion and a cell without any Cr contamination were characterized in the same manner. According to the impedance data, the polarization resistance for both cells, which were contaminated with Cr species, increased. The expected relationship between deposited amount of Cr and increase of polarization resistance was found. ICP-OES analysis proves the high reproducibility of the method as the Cr content is only a function of the Cr paste composition and almost independent of external poisoning conditions. Due to its scalability and reproducibility, this method is proposed to be a new tool for screening of cathode materials and the investigation of different stages of Cr poisoning prior to more sophisticated and time consuming investigations like stack tests.